2008
DOI: 10.1093/jpepsy/jsm130
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Reporting Practices of Methodological Information in Four Journals of Pediatric and Child Psychology

Abstract: Improvements in descriptive information have implications for interpretation, replication, and generalizability of research findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…For instance, all submissions should use a structured abstract format, and all should conform to the current APA Journal Article Reporting Standards (APA Publications and Communications Board Working Group on Journal Article Reporting Standards, 2008). Consistent with these guidelines and the findings of Raad, Bellinger, McCormick, Roberts, and Steele (2008), all empirical manuscripts should offer thorough descriptions of the sample, including (a) the population from which the sample was drawn; (b) the number of participants; (c) age, gender, ethnicity, and socioeconomic status of participants; (d) location of sample, including country and community type (rural=urban); (e) sample PAST, PRESENT, FUTURE identification=selection; (f) how participants were contacted; (g) incentives=rewards; (h) parent consent=child assent procedures and rates; (i) inclusion and exclusion criteria; and (j) attrition rate. Reliability and validity data are required for all measures.…”
Section: Current Jccap Focussupporting
confidence: 88%
“…For instance, all submissions should use a structured abstract format, and all should conform to the current APA Journal Article Reporting Standards (APA Publications and Communications Board Working Group on Journal Article Reporting Standards, 2008). Consistent with these guidelines and the findings of Raad, Bellinger, McCormick, Roberts, and Steele (2008), all empirical manuscripts should offer thorough descriptions of the sample, including (a) the population from which the sample was drawn; (b) the number of participants; (c) age, gender, ethnicity, and socioeconomic status of participants; (d) location of sample, including country and community type (rural=urban); (e) sample PAST, PRESENT, FUTURE identification=selection; (f) how participants were contacted; (g) incentives=rewards; (h) parent consent=child assent procedures and rates; (i) inclusion and exclusion criteria; and (j) attrition rate. Reliability and validity data are required for all measures.…”
Section: Current Jccap Focussupporting
confidence: 88%
“…Deficiencies in reports from clinical pediatric research have been found in various pediatric subspecialties including pediatric urology, pediatric orthopedics, and drug trials. [34][35][36][37] Generic reporting guidelines have been developed by groups of scientists, methodologists, and journal editors with the aim to improve the quality of research reports. There is now first evidence of a positive impact of such guidelines on reporting quality.…”
Section: Commentmentioning
confidence: 99%
“…[13] Analysis of reporting characteristics provides the current status of research publications in journals. Reporting characteristics were reviewed previously and published in a variety of journals in the fields of general medicine,[423] dentistry,[2426] and in secondary journals[27] that involved medical specialties such as anesthesiology,[2829] dermatology,[3034] emergency medicine,[3536] endocrinology,[37] gastroenterology,[38] hepatology,[32] ophthalmology,[3940] otorhinolaryngology,[4142] physiology,[43] pediatrics,[4445] pediatric dentistry,[46] pediatric psychology,[47] surgery,[4849] veterinary medicine[50] and also in allied health,[51] nursing[52] and rehabilitation. [53]…”
Section: Introductionmentioning
confidence: 99%
“…[56] Most of the studies focused on reporting of ethical issues,[1315242834444555] quality of reporting,[4691216182531374046485053] research methodology[7192032333536414547] and statistical issues,[82122262943] very few studies were focused on reporting characteristics for clinical topics such as diagnosis,[30384052] and/or treatment[5357] for diseases or disorders. [5759]…”
Section: Introductionmentioning
confidence: 99%